Fat Chance: The Rejuvenation of Irradiated Skin - Mimi R. Borrelli, MBBS, MSc; Ronak A. Patel, BS; Jan Sokol, BS; Dung Nguyen, MD; Arash Momeni, MD; Michael T. Longaker, MD, MBA; Derrick C. Wan, MD (Plastic and Reconstructive Surgery, Global Open, 2019)
Summary:. Radiotherapy (RT) helps cure and palliate thousands of patients with a range of malignant diseases. A major drawback, however, is the collateral damage done to tissues surrounding the tumor in the radiation field. The skin and subcutaneous tissue are among the most severely affected regions. Immediately following RT, the skin may be inflamed, hyperemic, and can form ulcers. With time, the dermis becomes progressively indurated. These acute and chronic changes cause substantial patient morbidity, yet there are few effective treatment modalities able to reduce radiodermatitis. Fat grafting is increasingly recognized as a tool able to reverse the fibrotic skin changes and rejuvenate the irradiated skin. This review outlines the current progress toward describing and understanding the cellular and molecular effects of fat grafting in irradiated skin. Identification of the key factors involved in the pathophysiology of fibrosis following RT will inform therapeutic interventions to enhance its beneficial effects.